The Influence Of Work Life’s Quality and Job Satisfaction Toward Nurses Performance in Inpatient Ward Edelweiss Hospital Bandung - Poerin, Neta Oktiyani; Sudjana, Grita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Hospital nurses in Indonesia are declining (2021 data), as well as in West Java Province (2022 data). This phenomenon (2021 data) also occurred at Edelweiss Hospital, Bandung (RS). The increasing demand for nursing staff and demands for high quality of service affect the performance of nurses (Brooks Anderson, 2005). Nurse job satisfaction plays an important role in supporting motivation and performance. This study aims to analyze the effect of quality of work life and job satisfaction on the performance of nurses in the Inpatient Installation at the Hospital. This study used a cross-sectional method with a descriptive analysis approach and partial and simultaneous correlation-regression through quantitative and qualitative methods. The entire population (census) of 54 nurses in the Inpatient Installation was used in this study. Data collection techniques through questionnaires and interviews were used. The results of the study showed that the quality of work life, job satisfaction, and nurse performance were in the "Good-Very Good" category. The results of the correlation-regression showed that the quality of work life and job satisfaction had a strong relationship with nurse performance with an r value of 0.809. The results of the research hypothesis test showed that the quality of work life and job satisfaction had a positive effect on nurse performance, with a p-value of 0.000 (p 0.05). This is in line with the theory of Brooks Anderson and Muller Mc Closkey. The study concluded that both quality of work life and job satisfaction have a positive impact on nurse performance. Suggestions for hospital management include additional management support in implementing policies, optimizing quality of work life, strengthening the conformity between SOPs and field practices, and strengthening work-life balance programs.